MENGEMBANGKAN SUMBER DAYA INSANI DALAM BISNIS: KONSTRUKS PEMIKIRAN TEOLOGIS - Djakfar, Muhammad (Fakultas Ekonomi, UIN Maliki Malang, 2013)
Business industry progress of the country not always runs same way with ethic rule and law, this reality is disadvantage. One of sources is the personal quality of religious back ground. In spite of that this writing to give solution which how to develope human resources developmant bocome spiritual personality in thinking and acting.Â The sources are taken from library text, media on line, electronic and paper media were critized in Islamic law or maqashid al-Syariah. Based on analized that recommended of developing the future human resources development can be hold by Islamic college, School as like honesty canteen, family and society. By this approach is hoped building the complete HRD in spitituality, knowledge, morality, professionality andÂ good Islamic relationship. Therefore they, human economic-materilistic, do economic activity as The Islamic law, theology approach, which bring their life to be good, humanity, ethic value and justice. We do hope.